Peningkatan Keaktifan Dan Hasil Belajar Ipa Melalui Strategi Team Games Tournament Pada Siswa Kelas IV SDN Blangu 1 Tahun Ajaran 2016/2017 - Adita, Andre Resa; , Drs. Mulyadi S.K. SH. M.Pd (2017)
This classroom action research aims (1) To increase the activity of learning science memalui strategy Team Games Tournamen (TGT) in the fourth grade students at SDN Blangu 1 (2) To improve learning outcomes IPA through a strategy of Team Games Tournamen (TGT) fourth grade students of SDN Blangu 1. the subject of this action research was grade IV SDN Blangu 1 totaling 30 students. Data collection using interviews, observation, testing, and documentation. In testing the validity of the data used triangulation and source triangulation techniques. Data were analyzed using interactive analysis include: data reduction, peyajian data, and drawing conclusions. The results of the research that has been done, the increased activity of learning that is at the pre cycle of 24.97% (8 students), the first cycle of 43.3% (13 students), and the second cycle 71% (23 students). Improved student learning outcomes in pre-cycle to 33.33% (10 students), the first cycle of 51.65% (16 students), and the second cycle 76.65% (23 students). It is concluded that Team Games Tournament strategy can enhance the activity and learning outcomes of fourth grade students at SDN Blangu 1.